The multifaceted roles of the HORMA domain in cellular signaling - Rosenberg, Scott C. (J Cell Biol, 2015)
The HORMA domain is a multifunctional protein–protein interaction module found in diverse eukaryotic signaling pathways including the spindle assembly checkpoint, numerous DNA recombination/repair pathways, and the initiation of autophagy. In all of these pathways, HORMA domain proteins occupy key signaling junctures and function through the controlled assembly and disassembly of signaling complexes using a stereotypical “safety belt” peptide interaction mechanism. A recent explosion of structural and functional work has shed new light on these proteins, illustrating how strikingly similar structural mechanisms give rise to radically different functional outcomes in each family of HORMA domain proteins.